Fundacje klasztorów Misjonarzy Oblatów Maryi Niepokalanej w Archidiecezji Poznańskiej w latach 1922-1939 - Zając, Paweł (Ecclesia. Studia z Dziejów Wielkopolski, 2010)
Polish Missionary Oblates of Mary Immaculate belonged initially to the religious provinces of their Congregation in Germany and Canada. Since the end of the 19th century they were involved greatly with the ministry to the Polish immigrants. After 1918 they pursued a project of founding a separate Polish province. Their first most important communities in Poland were organized with the support of the archbishops of Poznań and Gniezno and of civil authorities in Poznań. The reasons for choosing this area included its traditional patriotism and closeness to Silesia, which was the source of many early Oblate Polish vocations. The article depicts all the most important stages of Oblate foundations in the archdiocese of Poznań, which included among others the provincial house and two major seminaries.